POTENCIAL DE RISCO NA BIOACUMULAÇÃO DE METAIS EM PEIXES NO RIO AMAMBAI, ALTO RIO PARANÁ, BRASIL - RIVEROS, Adriana Fernandes; VIANA, Lucilene Finoto; CARDOSO, Claudia Andrea Lima; LIMA-JUNIOR, Sidnei Eduardo (ANAIS DO ENIC, 2020)
-